2010
DOI: 10.4251/wjgo.v2.i4.192
|View full text |Cite
|
Sign up to set email alerts
|

Appendiceal neuroendocrine tumors: Recent insights and clinical implications

Abstract: New insights emerged last decade that enriched our knowledge regarding the biological behavior of appendiceal neuroendocrine tumors (NETs), which range from totally benign tumors less than 1cm to goblet cell carcinomas which behave similarly to colorectal adenocarcinoma. The clinical implication of that knowledge reflected to surgical strategies which also vary from simple appendicectomy to radical abdominal procedures based on specific clinical and histological characteristics. Since the diagnosis is usually … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
41
0
5

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(46 citation statements)
references
References 37 publications
0
41
0
5
Order By: Relevance
“…However, a number of recent studies have reported a higher than expected rate of venous and/or lymphatic invasion (lymphovascular invasion) in GEP-NET samples obtained via endoscopic procedures [46]. In a case series from our own institution, we identified a lymphovascular invasion rate of approximately 30 % for GEP-NETs.…”
Section: Introductionmentioning
confidence: 66%
“…However, a number of recent studies have reported a higher than expected rate of venous and/or lymphatic invasion (lymphovascular invasion) in GEP-NET samples obtained via endoscopic procedures [46]. In a case series from our own institution, we identified a lymphovascular invasion rate of approximately 30 % for GEP-NETs.…”
Section: Introductionmentioning
confidence: 66%
“…Foregut NETs refer to tumors arising in the respiratory tract, thymus, thyroid, stomach, duodenum and pancreas. Midgut NETs develop in the small bowel, appendix and ascending colon (11), while hindgut tumors appear in the transverse, descending colon and rectum (12,13).…”
Section: Discussionmentioning
confidence: 99%
“…Tübüler karsinoid hücrelerinin çoğu nöroendokrin özellikte iken GHKT' de hücrelerin %25'inden azı nöroendokrin özellik gösterir (3,22,23).…”
Section: Discussionunclassified
“…Olgumuz da literatürle uyumlu olarak bu özelliklere sahip değildi. GHKT 'lerde MUC2 pozitif, p53 %5-10 pozitif, MUC1 negatif iken, adenokarsinomlarda p53 pozitif, MUC1 pozitif, MUC2 % 5 pozitiftir (3,8,22,24).…”
Section: Discussionunclassified